2018
DOI: 10.1186/s13756-018-0357-6
|View full text |Cite
|
Sign up to set email alerts
|

How long is enough? Identification of product dry-time as a primary driver of alcohol-based hand rub efficacy

Abstract: BackgroundThe World Health Organization has called for the development of improved methodologies to evaluate alcohol-based handrub (ABHR) efficacy, including evaluation at “short application times and volumes that reflect actual use in healthcare facilities”. The objective of this study was to investigate variables influencing ABHR efficacy, under test conditions reflective of clinical use.MethodsThe test product (60% V/V 2-propanol) was evaluated according to a modified EN 1500 methodology, where application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…The participants scored noticeably low on the correct procedure of hand hygiene using alcohol hand rub, tested on many dimensions such as drying time and concentration of alcohol. Appropriate alcohol concentration and drying time are the primary drivers of efficacy [ 11 ]. It is essential to understand that efficacy also depends on the alcohol quantity applied.…”
Section: Discussionmentioning
confidence: 99%
“…The participants scored noticeably low on the correct procedure of hand hygiene using alcohol hand rub, tested on many dimensions such as drying time and concentration of alcohol. Appropriate alcohol concentration and drying time are the primary drivers of efficacy [ 11 ]. It is essential to understand that efficacy also depends on the alcohol quantity applied.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Tables 1 , 2 and 3 , this included two parallel design [ 16 , 17 ], one crossover [ 18 ] and eight within-subject [ 19 26 ] RCTs, and one parallel design [ 27 ], one crossover [ 28 ] and seven within-subject [ 29 35 ] NRTs. Apart from one study [ 17 ] conducted in China, all included evidence derives from high income countries, including Australia (n = 1) [ 28 ], Austria (n = 2) [ 25 , 33 ], France (n = 1) [ 31 ], Germany (n = 3) [ 16 , 18 , 32 ], Switzerland (n = 5) [ 23 , 24 , 26 , 29 , 30 ], UK (n = 3) [ 27 , 34 , 35 ] and USA (n = 2) [ 19 , 22 ], while two were multisite studies conducted in the Netherlands and UK [ 21 ], and in Germany and USA [ 20 ]. Despite searching for studies published since 1980, the publication year of the included studies ranged from 2003 to 2020, with most studies (n = 15) published within the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…60% (v/v) isopropanol; 2. 80% (v/v) ethanol + 1.45% (v/v) glycerol + 0.125% (v/v) hydrogen peroxide (each in liquid, gel & foam format) Application technique 6-steps; Mean drying times (seconds) , for 2 tested ABHRs in 3 formats) 1.5 ml: 19.67–31.53 3 ml: 35.07–63.13 Increasing the volume increased the drying time (P < 0.001) Jain, Clezy & McLaws (2018) [ 28 ] Australia Crossover NRT Clinical 40 HCWs 2 dispenser pump presses vs. 3 dispenser pump presses Bacterial load on hands Fingertips (cultured for MRSA and VRE) Product foam ABHR; product contents not reported Application time rubbed until hands were dry Application technique 6-steps Number of plates with MRSA or VRE growth: 2 dispenser pumps: 2/40 grew 1 colony-forming unit of MRSA 3 dispenser pumps: No growth Suchomel et al (2018) [ 33 ] Austria Within-subject NRT Laboratory 15 volunteers 1ml 2 ml 3 ml 1) Bacterial load on hands; 2) Hand size; 3) Drying time 1) Fingertips; 2) Hand surface area calculation Small < 375cm 2 Medium 376–424 cm 2 Large > 425 cm 2 ; 3) Time measured until participants reported that their hands felt dry Product ABHR 2-propanol 60% (v/v) liquid; Application time not applicable (drying time measured as outcome) Application technique 6-steps Artificial contamination ( E. coli ) Mean log 10 RF (SD) 1ml: 1.99 (0.66) 2 ml: 2.96 (0.84) 3 ml: 3.28 (0.96) Mean log 10 RFs were greater when larger volumes were used (P < 0.0001), but no significant difference between 2 ml & 3 ml (P = 0.08) Hand size and log 10 RF (P = 0.698). Hand size and RF accounting for dry-times and volumes (R 2 = 77%, P = 0.403) Mean (SD) drying (seconds) 1ml 24 (7) 2 ml 50 (14) 3 ml 67 (20) (P ≤ 0.030) Mean drying times were greater when larger application volumes were used (P < 0.0001) Regardless of volume Reduction fraction increased 0.29 log 10 per 10 s increased drying time Kenters et al (2020) [ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 One recent study found a linear relationship between dry-time and the log reduction of bacteria on hands that was independent of application volume. 3 Limited evidence suggests that there is considerable variation in the amount of ABHR that is used per application by health care providers.…”
Section: Introductionmentioning
confidence: 99%